From roadman to royalties: Inter-representational value and the hypercapitalist impulses of grime - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2021)
This paper explores how digital media can cause the representational value of rap artists to be transformed. Ubiquitous access to digital recording, production and distribution technologies grants rappers an unprecedented degree of representational autonomy, meaning they are able to integrate the street aesthetic into their lyrics and music videos, and thus create content that offers a more authentic representation of their (past) lives. Sidestepping the mainstream music industry, the digital enables these integrations and bolsters the hypercapitalist impulses of content creators. I illustrate these ideas through a case study of grime artist, Bugzy Malone, who uses his music to narrate his evolution from a life of criminality (selling drugs on the street; a “roadman”), to one in which his representational value is recognised by commercial brands who want to partner with him because of his street credibility (collecting “royalties”). Bugzy Malone’s commercial success is not predicated on a departure from his criminal past, but the deliberate foregrounding of it as a marker of authenticity. The representational autonomy provided by digital media can therefore enable artists to maximise the affective cachet of the once-criminal self.